Mycoplasma genitalium antibiotic resistance-associated mutations in genital and extragenital samples from men-who-have-sex-with-men attending a STI clinic in Verona, Italy - Sandri, Angela; Carelli, Maria; Visentin, Alessandro; Savoldi, Alessia; De Grandi, Gelinda; Mirandola, Massimo; Lleo, Maria M.; Signoretto, Caterina; Cordioli, Maddalena (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Mycoplasma genitalium (MG) is one of the most warning emerging sexually transmitted pathogens also due to its ability in developing resistance to antibiotics. MG causes different conditions ranging from asymptomatic infections to acute mucous inflammation. Resistance-guided therapy has demonstrated the best cure rates and macrolide resistance testing is recommended in many international guidelines. However, diagnostic and resistance testing can only be based on molecular methods, and the gap between genotypic resistance and microbiological clearance has not been fully evaluated yet. This study aims at investigating the relationship between MG antibiotic resistance and microbiological clearance amongst men-who-have-sex-with-men (MSM). Methods: From 2017 to 2021, genital (urine) and extragenital (pharyngeal and anorectal swabs) specimens were provided by (MSM) attending an STI clinic at the Verona University Hospital, Verona, Italy. A total of 1040 MSM were evaluated and 107 samples from 96 subjects resulted positive for MG. Among the MG-positive samples, all those available for further analysis (n=47) were considered for detection of mutations known to be associated with macrolide and quinolone resistance. 23S rRNA, gyrA and parC genes were analyzed by Sanger sequencing and Allplex™ MG & AziR Assay (Seegene). Results: 96/1040 (9.2%) subjects tested positive for MG in at least one anatomical site. MG was detected in 107 specimens: 33 urine samples, 72 rectal swabs and 2 pharyngeal swabs. Among them, 47 samples from 42 MSM were available for investigating the presence of mutations associated with macrolide and quinolone resistance: 30/47 (63.8%) showed mutations in 23S rRNA while 10/47 (21.3%) in parC or gyrA genes. All patients with positive Test of Cure (ToC) after first-line treatment with azithromycin (n=15) were infected with 23S rRNA-mutated MG strains. All patients undergoing second-line moxifloxacin treatment (n=13) resulted negative at ToC, even those carrying MG strains with mutations in parC gene (n=6). Conclusion: Our observations confirm that mutations in 23S rRNA gene are associated with azithromycin treatment failure and that mutations in parC gene alone are not always associated with phenotypic resistance to moxifloxacin. This reinforces the importance of macrolide resistance testing to guide the treatment and reduce antibiotic pressure on MG strains.